Analgesic properties of a food grade lecithin delivery system of Zingiber officinale and Acmella oleracea standardized extracts in rats. Issue 18 (17th September 2021) - Lobina, Carla; Sau, Roberta; Fara, Federica; Maccioni, Paola; Carai, Mauro A. M.; Colombo, Giancarlo
Abstract: This study investigated whether (i) the 5:1 combination of standardized extracts of Zingiber officinale and Acmella oleracea is endowed with analgesic effects and (ii) the phospholipid-based formulation of Zingiber officinale and Acmella oleracea extracts (ZAP) potentiated the analgesic effects of the plain extract combination (PEC). To this end, rats were exposed to acute pain (Tail Flick test) and chronic, inflammatory pain [Von Frey monofilament test and Randall–Selitto paw pressure test in rats treated intraplantarily with complete Freund's adjuvant (CFA)]. The plain combination of per se ineffective doses of the two extracts produced analgesic effects in healthy rats. ZAP was more potent and effective than the corresponding doses of PEC. ZAP also produced analgesic effects in CFA-treated rats. Studies are now warranted to assess whether the analgesic properties of ZAP may generalize to humans. Graphical Abstract: